(untitled) (The Review of Diabetic Studies, 2025)
Pediatric emergencies present unique challenges due to children’s distinct physiological and developmental characteristics. Paramedics are often the first healthcare professionals to respond, making their role crucial in stabilizing critically ill or injured children. This review explores the scope of pediatric emergencies managed by paramedics, the challenges encountered, and the outcomes achieved. Key challenges include limited pediatric exposure in training, difficulties in assessment due to communication barriers, medication dosing complexities, equipment availability, and the psychological stress of managing critically ill children. Despite these obstacles, evidence shows that paramedics can achieve favorable outcomes when supported by robust training, protocols, and system integration. Strategies such as simulation-based education, decision-support tools, and interdisciplinary collaboration are essential to improving both confidence and competency in pediatric prehospital care. Ultimately, strengthening paramedic preparedness and addressing systemic barriers can enhance survival rates and long-term outcomes in pediatric emergencies.